A preliminary RCT of a mind body skills based intervention addressing mood and coping strategies in patients with acute orthopaedic trauma. Issue 4 (April 2015) - Vranceanu, Ana-Maria; Hageman, Michiel; Strooker, Joost; ter Meulen, Dirk; Vrahas, Mark; Ring, David
Abstract: Objective: To test the acceptability and feasibility of a mind body skills-based intervention (RRCB) and estimate its preliminary effect in reducing disability and pain intensity as compared to standard care (SC) in patients with acute musculoskeletal trauma. Design: Randomised controlled trial. Setting: Level I trauma centre. Patients: Adult patients with acute fractures at risk for chronic pain and disability based on scores on two coping with pain measures who presented to an orthopedic trauma center and met inclusion and exclusion criteria. Intervention: Participants were randomied to either RRCB with SC or SC alone. Main outcome measurement: Disability (short musculoskeletal functional assessment, SMFA) and pain (Numerical Analogue Scale). Secondary outcome measures: coping strategies (Pain Catastrophizing Scale, PCS and Pain Anxiety Scale, PAS) and mood (CESD Depression and PTSD checklist). Results: Among the 50 patients consented, two did not complete the initial assessment. Of these, the first four received the intervention as part of an open pilot and the next 44 were randomised (24 RRCBT and 20 UC) and completed initial assessment. We combined the patients who received RRCB into one group, N = 28. Of the entire sample, 34 completed time two assessments (24 RRCBT and 10 SC). The RRCB proved to be feasible and accepted (86% retention, 28 out of 24 completers). Analyses of covariance ANCOVA showed a significant ( p < 05) improvement and large effect sizes for all time two main study variables (.2–.5) except pain with activity where the effect size was medium (.08). Improvement for pain at rest was not significantly higher in the RRCB as compared to the control, for a small effect size (.03). Conclusion: The RRCB is feasible, acceptable and potentially efficacious. Level of evidence: Level 1 prognostic.